2014
DOI: 10.1302/0301-620x.96b4.32895
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between surface properties of standard, vitamin E blended and oxidised ultra high molecular weight polyethylene used in total joint replacement and adhesion ofStaphylococcus aureusandEscherichia coli

Abstract: AMInterplay between surface properties of standard, vitamin E blended and oxidised ultra high molecular weight polyethylene used in total joint replacement and adhesion of Staphylococcus aureus and Escherichia coli. JOURNAL OF BONE AND JOINT SURGERY-BRITISH VOLUME (2014) 96-B (4) DOI: 10.1302/0301-620X.96B4/32895The definitive version is available at:http://www.bjj.boneandjoint.org.uk/cgi/doi/10.1302/0301-620X.96B4/32895 AbstractThis study was aimed at assessing the different adhesive strength of some of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 28 publications
3
15
0
Order By: Relevance
“…For example, Banche et al and Gómez-Barrena et al reported that vitamin E-doped or -blended PE had the potential to reduce bacteria adhesion [12][13][14]. However, vitamin E blending has also been shown to reduce bacterial adhesion by only about one-tenth or less [12][13][14][15][16]. Moreover, Williams et al reported that vitamin E-blended PE did not have the ability to reduce biofilm formation [16], which was consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…For example, Banche et al and Gómez-Barrena et al reported that vitamin E-doped or -blended PE had the potential to reduce bacteria adhesion [12][13][14]. However, vitamin E blending has also been shown to reduce bacterial adhesion by only about one-tenth or less [12][13][14][15][16]. Moreover, Williams et al reported that vitamin E-blended PE did not have the ability to reduce biofilm formation [16], which was consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies evaluated bacteria adherence to vitamin E-blended PE [12][13][14][15][16]. For example, Banche et al and Gómez-Barrena et al reported that vitamin E-doped or -blended PE had the potential to reduce bacteria adhesion [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations